MICROVESICLES GENERATED FOLLOWING TRAUMATIC BRAIN INJURY INDUCE PLATELET DYSFUNCTION VIA ADP RECEPTOR: Platelet Dysfunction Following TBI - Martin, Grace E (J Trauma Acute Care Surg, 2019)
INTRODUCTION: Traumatic brain injury (TBI) can result in an acute coagulopathy including platelet dysfunction that can contribute to ongoing intracranial hemorrhage. Previous studies have shown ADP-induced platelet aggregation to be reduced after TBI. In addition, circulating microvesicles (MVs) are increased following TBI and have been shown to play a role in post-TBI coagulopathy and platelet function. We hypothesized that post-TBI MVs would affect platelet aggregation in a murine head injury model. METHODS: Moderate TBI was performed using a weight-drop method in male C57BL6 mice. Whole blood, plasma, MVs, and MV-poor plasma were isolated from blood collected 10 minutes following TBI and were mixed separately with whole blood from uninjured mice. Platelet aggregation was measured with Multiplate impedance platelet aggregometry in response to adenosine diphosphate (ADP). The ADP P2Y(12) receptor inhibitor, R-138727, was incubated with plasma and MVs from TBI mice, and platelet inhibition was again measured. RESULTS: Whole blood taken from 10 minute post-TBI mice demonstrated diminished ADP-induced platelet aggregation compared to sham mice. When mixed with normal donor blood, post-TBI plasma and MVs induced diminished ADP-induced platelet aggregation compared to sham plasma and sham MVs. By contrast, the addition of post-TBI MV-poor plasma to normal blood did not change ADP-induced platelet aggregation. The observed dysfunction in post-TBI ADP platelet aggregation was prevented by the pretreatment of post-TBI plasma with R-138727. Treatment of post-TBI MVs with R-138727 resulted in similar findings of improved ADP-induced platelet aggregation compared to non-treated post-TBI MVs. CONCLUSION: ADP-induced platelet aggregation is inhibited acutely following TBI in a murine model. This platelet inhibition is reproduced in normal blood by the introduction of post-TBI plasma and MVs. Furthermore, observed platelet dysfunction is prevented when post-TBI plasma and MVs are treated with an inhibitor of the P2Y(12) ADP receptor. Clinically observed post-TBI platelet dysfunction may therefore be partially explained by the presence of the ADP P2Y(12) receptor within post-TBI MVs. LEVEL OF EVIDENCE: III